Effect of Urea with Various Doses on Skeletonema costatum Cell Growth - Mila Rosa; Sofyan Husein Siregar; Irvina Nurrachmi (Jurnal Perikanan dan Kelautan, 2021)
This research was conducted in March 2020 at BPBALP Teluk Buo, West Sumatera. This research aimed to determine the best dose for urea usage on S. costatum cell growth. The method used in this research was an experimental method using Completely Randomized Design (CRD) with one factor, which was the various doses of urea fertilizer consisting of five treatments with three replications. Urea various doses used were 0 ppm (control treatment), 40 ppm (treatment A), 60 ppm (treatment B), 80 ppm (treatment C), and 100 ppm (treatment D) totaling 15 treatment units. The tested organism in this research was S. costatum. The container used was a plastic jar with 2 liters capacity. The parameters tested in this research were the maximum cell population density achieved by seven days of maintenance, absolute growth rate, relative growth rate, and specific growth rate. The results showed that the best cell density was found at the treatment D (100 ppm), which was 1,228 x 104 cells / mL and the lowest cell density was in the control treatment (without urea) which was 533 x 104 cells / ml. The results of water quality measurements during the study were still in an adequate range and met the maintenance requirements of S. costatum. The range of water quality parameters were salinity 26-28 ppt, temperature of 25-27oC, and pH of 8